PENANAMAN PENDIDIKAN KARAKTER MENGGUNAKAN MEDIA PAPAN PRESTASI DALAM PEMBELAJARAN TEMATIK KELAS 3 - Nur’aini, Miftahul; Kamidjan, Kamidjan; Raharja, Hawwin Fitra (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
Education and schools that are expected to be able to make students well-behaved and smart in actual learning only focus on developing the cognitive knowledge of their students without being able to overcome the moral development of their students, this is evidenced by the many reports about juvenile delinquency that occur in Indonesia. So from these problems character education began to be carried out according to the 2003 SISDIKNAS Law. Given the lack of character of the nation's children, the task and responsibility of teachers is to inculcate character values early on into various activities in schools. Good learning must be supported by several aspects, namely processional teachers, the existence of learning resources and learning media. This research uses descriptive qualitative research methods with the type of field research. This study aims to describe the process of implementing character education planting using achievement board media in class 3 thematic learning at SDN Cukir 1. The use of achievement board media as character education planting in thematic learning can be applied through the following steps: Explaining the meaning and purpose of character education, introduce 18 character values, look for examples of behavior that reflect each value and introduce achievement board media and how to play them. Achievement board media have a positive impact such as lightening the task of the teacher, students are more active in learning, the values of characters are more striking in students, more easily understood and applied in student life